Quality checking and inspection based on machine vision technique to determine tolerance value using single ceramic cup - Mohd Ali, Nursabillilah; Karis, Mohd Safirin; Wong, Gao Jie; Bahar, Mohd Bazli; Sulaiman , Marizan; Mat Ibrahim, Masrullizam; Zainal Abidin, Amar Faiz (Asian Research Publishing Network (ARPN), 2016)
The development of an algorithm for inspection and quality checking using machine vision was discussed in this paper, in which the design of the algorithm is to detect the sign of defect when a sample of the product is used for inspection purposes. It is also designed to track specific color of product and conduct the inspection process. Programming language of python and open source computer vision library were used to design the inspection algorithm based on the algorithm required to achieve the inspection task. Illumination and surrounding environment were considered during the design as it may affect the quality of image acquisitioned by image sensor. Experiment and set-up by using CMOS image sensor were conducted to test the designed algorithm for effectiveness evaluation. The experimental results were obtained and are represented in graphical form for further analysis purposes. Besides, analysis and discussion were made based on the obtained results through the experiments. The designed algorithm is able to perform the inspection by sample object detection and differentiate between good and defect unit.